Potential Use of the Gel Extract of Butterfly Pea Flower as Topical Therapy to Prevent Photodamage by Downregulating TNF-α and Caspase-3 Expression Levels in UVB-Exposed Rats - Cahyani, Elvana; Putra, Agung; Subchan, Prasetyowati (Makara Journal of Health Research, 2023)
Background: Prolonged exposure to UVB radiation causes DNA damage in skin cells by raising the levels of reactive oxygen species, resulting in the production of inflammatory factors and skin issues. Plant extracts are frequently used to counteract photodamage due to their antioxidant properties. One example is the floral extract of the butterfly pea plant, which contains flavonoid antioxidants. However, the effect of the extract on inflammatory factors is unknown. This study investigated how tumor necrosis factor-alpha (TNF-α) and caspase-3 expression changed when a butterfly pea flower extract gel was applied topically to UVB-exposed animals. Methods: Experimental and control groups were tested. The healthy group was not exposed to UVB. The negative controls and treatments 1 and 2 were exposed daily for 5 days at a minimal erythema dose of 160 mJ/cm2 and then treated with a gel-based extract containing 5% and 10% of the extract, respectively. A 96% ethanol solution was used during the maceration step for the extraction. Real-Time Quantitative Reverse Transcription PCR was used to examine gene expression levels in the skin tissue on day 14. Results: The expression levels of TNF-α and caspase-3 decreased in the treatment group, and higher doses of the extract had a greater effect. Conclusions: The gel extract considerably reduced the UVB-induced TNF-α and caspase-3 production in rats.